The Satisfaction on Online Shopping Platforms of ABM Students at Bestlink College of the Philippines S.Y. 2022 - 2023: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The pandemic has made online shopping more popular as people prefer to shop online ratherthan buy at a physical store to avoid getting infected by the virus. This study aims to determinethe satisfaction of online shopping platforms for ABM students.Furthermore, results showed that the proposed output of satisfaction on online shoppingplatforms would help online businesses to improve and to be recognized in terms of spendingless on the product and service’s cost, wider range and easier distribution of service, andsatisfy the necessities and demands of their customers with the use of online shoppingplatforms.Respondents need to be aware of what they purchase online that may satisfy them. Onlineshopping platforms that they need to use are trusted and convenient platforms for them tochoose the right products. Consumers need to know about the products they will purchaseonline.
Keywords: Business